Green hematite depression for reverse selective flotation separation from quartz by locust bean gum - Mehrdad Kordloo; Gholamreza Khodadadmahmoudi; Ehsan Ebrahimi; Ali Rezaei; Arash Tohry; Saeed Chehreh Chelgani (Scientific Reports, 2023)
Abstract Reverse cationic flotation is currently the main processing technique for upgrading fine hematite from silicates. Flotation is known as an efficient method of mineral enrichment that deals with possibly hazardous chemicals. Thus, using eco-friendly flotation reagents for such a process is an emerging need for sustainable development and green transition. As an innovative approach, this investigation explored the potential of locust bean gum (LBG) as a biodegradable depressant for the selective separation of fine hematite from quartz through reverse cationic flotation. Various flotation conditions (micro and batch flotation) were conducted, and the mechanisms of LBG adsorption have been examined by different analyses (contact angle measurement, surface adsorption, zeta potential measurements, and FT-IR analysis). The micro flotation outcome indicated that the LBG could selectively depress hematite particles with negligible effect on quartz floatability. Flotation of mixed minerals (hematite and quartz mixture in various ratios) indicated that LGB could enhance separation efficiency (hematite recovery > 88%). Outcomes of the surface wettability indicated that even in the presence of the collector (dodecylamine), LBG decreased the hematite work of adhesion and had a slight effect on quartz. The LBG adsorbed selectively by hydrogen bonding on the surface of hematite based on various surface analyses.